2015
DOI: 10.1523/jneurosci.0640-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for Developmental Topographic Disorientation

Abstract: Developmental topographic disorientation (DTD) is a life-long condition in which affected individuals are severely impaired in navigating around their environment. Individuals with DTD have no apparent structural brain damage on conventional imaging and the neural mechanisms underlying DTD are currently unknown. Using functional and diffusion tensor imaging, we present a comprehensive neuroimaging study of an individual, J.N., with well defined DTD. J.N. has intact scene-selective responses in the parahippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Specifically, the core network included regions like the PHG, RSC, and HIP, which are primarily responsible for three key components for successful navigation: visual scene processing (Epstein and Kanwisher 1998), spatial orientation (Marchette et al 2014;Kim et al 2015), cognitive map (O'Keefe and Dostrovsky 1971; Ekstrom et al 2003), respectively. Both neuroimaging and neuropsychological studies have suggested the critical behavioral importance of the core network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the core network included regions like the PHG, RSC, and HIP, which are primarily responsible for three key components for successful navigation: visual scene processing (Epstein and Kanwisher 1998), spatial orientation (Marchette et al 2014;Kim et al 2015), cognitive map (O'Keefe and Dostrovsky 1971; Ekstrom et al 2003), respectively. Both neuroimaging and neuropsychological studies have suggested the critical behavioral importance of the core network.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, the RSC has been highlighted as an important area for navigation and route learning (Maguire et al 1998;Maguire 2001;Cain et al 2006;Cooper and Mizumori 2001;O'Craven and Kanwisher 2000). For instance, recent studies suggests that the RSC anchors our sense of direction to local environment (Marchette et al 2014), and that an alteration of the RSC's functional properties may serve as the neural basis for developmental topographic disorientation (DTD) (Kim et al 2015). Previous neuropsychological findings also showed that patients with damage in the RSC are unable to describe the relationship between locations and exhibited spatial navigation impairment (Takahashi et al 1997;Aguirre and D'Esposito 1999;Valenstein et al 1987;Vann et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As control regions, retinotopic early visual areas (V1-V4) and the face-selective fusiform face area (FFA) were defined for each participant. Retinotopic areas were defined using a standard topographic mapping procedure from a separate scanning session (8,37), and FFA was defined based on the contrast faces vs. scenes. Figure 2 depicts the locations and BOLD time courses of LOC and PPA for LSJ and a representative control participant C1 for visualization purposes.…”
Section: Visual Selectivitymentioning
confidence: 99%
“…This adaptation phenomenon (also called repetition suppression or repetition attenuation) can be considered a form of rapid learning and a signature of perceptual memory for previously viewed stimuli. Adaptation has been observed in many visual regions including the lateral occipital cortex (LOC) for repeated presentations of objects (e.g., [1][2][3][4][5] and in the parahippocampal place area (PPA) for repeated presentations of scenes [6][7][8]. Adaptation occurs not only when a stimulus is repeated immediately (with no intervening stimuli), but also after a time lag of several minutes or longer during which intervening stimuli are presented (e.g., [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In more detail, lesions restricted to the hippocampus in humans result only in slight navigation impairments in familiar environments, but rather strongly impair learning or imagining new trajectories (Bohbot & Corkin, 2007;Clark & Maguire, 2016;Maguire, Intraub, & Mullally, 2016;Spiers & Maguire, 2006;Teng & Squire, 1999). In contrast, lesions in regions such as the parietal cortex or the retrosplenial cortex produce strong topographical disorientation in both familiar and new environments (Aguirre & D'Esposito, 1999;Habib & Sirigu, 1987;Kim, Aminoff, Kastner, & Behrmann, 2015;Maguire, 2001;Takahashi, Kawamura, Shiota, Kasahata, & Hirayama, 1997). This suggests that the core navigation processes (which may include transformations from allocentric representations to egocentric motor commands) is performed independently by neocortical (including parietal cortex) areas outside the hippocampus, which may utilize hippocampal information related to recent memories (Ekstrom, Arnold, & Iaria, 2014;Miller et al, 2013;Rolls & Wirth, 2018).…”
mentioning
confidence: 99%